Kebijakan Peningkatan Proporsi Penerimaan Non-Utama PTKIN BLU: Mengurangi Ketergantungan pada UKT Melalui Penguatan Unit Bisnis - Nifia, Herlinda (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper presents a study on the policy of increasing the proportion of revenue from non-educational services (supporting services) at State Islamic Religious Colleges (PTKIN) with the status of Public Service Agency (BLU). The purpose of this study is to achieve the target of BLU management, namely to provide financially sustainable public services. The writing methodology used is qualitative with a descriptive approach, utilizing secondary data and SWOT analysis to identify internal and external factors that influence the management of supporting business units at PTKIN BLU. The results of the study indicate that the low proportion of BLU revenue is caused by two main factors, namely: suboptimal management of business units and limited human resource competencies. Based on these findings, several alternative policies are proposed, including the development of industry-based research and innovation clusters, internal and external regulatory reforms for the professionalization of business unit management, reform of the organizational structure of business units, and diversification of business unit types. The main recommendation proposed is internal and external regulatory reforms for the professionalization of business unit management. These are addressed to the Ministry of Finance as the BLU Financial Supervisor and the Ministry of Religious Affairs.